Synthesis of Acetaminophen Analogues Containing α-Amino Acids and Fatty Acids for Inhibiting Hepatotoxicity - Jung, Seunghee; Kawashima, Yuya; Noguchi, Takuya; Imai, Nobuyuki (Synthesis, 2019)
Acetaminophen is a popular antipyretic analgesic medicine that has weaker anti-inflammatory properties and lower incidence of side effects than nonsteroidal anti-inflammatory drugs (NSAIDs). However, acetaminophen causes hepatotoxicity due to the reactive metabolite N-acetyl-p-benzoquinone imine (NAPQI). We have obtained acetaminophen analogues in 57–99% yields by using aniline derivatives with protected α-amino acids and fatty acids via the corresponding mixed carbonic carboxylic anhydrides in aqueous MeCN. We have also succeeded in synthesizing AM404 analogues in 76–97% yields, which are expected to be promising candidates for reducing hepatotoxicity.
Keywords: acetaminophen; hepatotoxicity; α-amino acid; fatty acid; AM404